Shunt DC motor speed control methods using MATLAB: article / Umair Rafeeq Muhammad - Muhammad, Umair Rafeeq (2010)
This paper describes the simulation of DC motor speed control using Matlab Simulink. The three most common speed control methods are filed resistance control, armature voltage control, and armature resistance control. The interface program is designed so that the user can vary all the parameters of the circuits using the program and display the various characteristics.